A Computational Investigation of the Binding of the Selenium Analogues of Ergothioneine and Ovothiol to Cu(I) and Cu(II) and the Effect of Binding on the Redox Potential of the Cu(II)/Cu(I) Redox Couple - Jacqueline Wiebe; Vasyl Zaliskyy; Eric A. C. Bushnell (Journal of Chemistry)
The complexes formed from the binding of ovoselenol (OSeH) and ergoseloneine (ESeH) to Cu(II) and Cu(I) have been investigated with DFT methods. From the calculated thermodynamics, the binding of OSeH and ESeH to Cu(II) and Cu(I) ions increases the reduction potential for the Cu(II)/Cu(I) redox couple. The calculated reduction potentials for the Cu(II)(OSe)2/Cu(I)(OSeH)3+ and Cu(II)(ESe)2/Cu(I)(ESeH)3+ redox couples were found to be 1.15 V and 1.24 V in a dilute aqueous solution. By combining the half reactions for the oxidation of OSeH to the diselenide OSeSeO with the reduction of Cu(II)(OSe)2 to Cu(I)(OSeH)3+, the calculated EMF was 0.90 V. For the oxidation of ESeH to the diselenide ESeSeE with the concomitant reduction of Cu(II)(ESe)2 to Cu(I)(ESeH)3+, the calculated EMF was 0.67 V. Thus, for both systems, the reduction of Cu(II) to Cu(I) with concomitant formation of either diselenide is thermodynamically favourable, and it is expected that both OSeH and ESeH are suitable for the protection against copper induced oxidative damage. As a result, the inhibition of the recycling of Cu(I) to Cu(II) is thermodynamically favourable in the presence of OSeH and ESeH.